2021
DOI: 10.3389/fpls.2021.626149
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Levels Regulate Sugar Metabolism and Transport in the Shoot Tips of Crabapple Plants

Abstract: To comprehensively understand the responses of carbohydrate metabolism and transport to different levels of nitrogen supply in growing shoot tips of crabapple (Malus hupehensis Rehd), enzyme activities and related genes involved in the sugar metabolism pathway were investigated. The nitrogen and chlorophyll content of plants increased with increasing nitrogen supply. High nitrogen application increased the net photosynthesis rate and the growth rate of shoot tips but decreased the synthesis capability of sucro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 53 publications
3
31
0
Order By: Relevance
“…The application of NH 4 + /NO 3 − ratios have been considered to be of paramount importance to reduce the environmental effect and improved the N use efficiency [ 67 ]. Plant primary and secondary metabolic contents have been reduced when applying only a single form of N or when applying it in excess without mixing the NH 4 + /NO 3 − ratios due to internal competition for plants [ 68 ]. In the present study, sugar-related compounds (sucrose, fructose, lactulose, and maltose) in lettuce identified and analyzed via GC-MS and UPLC VION LC-MS/MS.…”
Section: Discussionmentioning
confidence: 99%
“…The application of NH 4 + /NO 3 − ratios have been considered to be of paramount importance to reduce the environmental effect and improved the N use efficiency [ 67 ]. Plant primary and secondary metabolic contents have been reduced when applying only a single form of N or when applying it in excess without mixing the NH 4 + /NO 3 − ratios due to internal competition for plants [ 68 ]. In the present study, sugar-related compounds (sucrose, fructose, lactulose, and maltose) in lettuce identified and analyzed via GC-MS and UPLC VION LC-MS/MS.…”
Section: Discussionmentioning
confidence: 99%
“…We think that on the one hand, the decreases in F6P and G6P contents can be attributed to the lower efficiency of hexose phosphorylation by hexokinase rather than the reduction in glucose supply. On the other hand, under warming conditions, A. faxoniana growing at high altitudes possibly consumes less energy than that growing at low altitude ( Zhao et al, 2020 ; Zhang et al, 2021 ). Therefore, A. faxoniana at low altitude need to obtain more energy to cope with warming, whereas it is most likely to adopt an energy conservation strategy at high altitude.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, K promoted the translocation of photosynthate to the fruit, as demonstrated by a significant increase in 13 C partitioning in the fruit due to the important role of K in photosynthate transport . Sorbitol is an important form of carbohydrate transport in apple and many other fruit tree species of the Rosaceae family . We determined the expression of MdSUTs and MdSOTs in leaves and fruits and found that high N suppressed the expression of MdSUT1 , MdSUT2 , MdSUT3 , and MdSOT1 , and K effectively alleviated this suppression.…”
Section: Discussmentioning
confidence: 98%